IMPROVING STUDENT'S READING INTEREST THROUGH THE JIGSAW COOPERATIVE LEARNING MODEL IN ELEMENTARY SCHOOL - Gustiana, Asep Deni; Rahman, Rahman; Hartati, Tatat; Supriatna, Nana (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
The habit of writing and reading in Indonesian society is still very low or not fully developed. In the interest of realizing a generation who likes to read, surely what must be grown first is the interest in reading in each individual. This problem encourages teachers to be able to provide optimal stimulus in fostering interest in reading in student from an early age while still prioritizing child-centered learning. This research implemented a jigsaw cooperative learning model. The research design used is Classroom Action Research (CAR) which includes two research cycles. The results second cycle show that 87% of student managed to reach the good category. Research using the Jigsaw Cooperative learning model on student's reading interest showed a significant increase. Based on the results of the research above, it can be concluded that the application of the Jigsaw cooperative learning model can increase student's reading interest.